INTENSIFIKASI PEMUNGUTAN PAJAK AIR TANAH SEBAGAI UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA TOMOHON - Panekenan, Heine Glorina; Lambey, Linda; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Intensifying the Ground Water Tax Collection is an effort in increasing and optimizing revenue by collecting the tax attentively, strictly, and deliberately. The implementation of intensifying the ground water tax collection in Tomohon City, especially at Local Financial Agency of Tomohon City, can be considered acceptable realizing the increases in the ground water tax income this year. This research method used in this thesis was descriptive method which is collecting the data from research outcome then analyzes it. Furthermore, a conclusion is drawn and the research type used was descriptive qualitative. The research findings showed that the process of intensifying the ground water tax collection at Local Financial Agency of Tomohon City is well implemented and according to applied regulation even though the goal set is not achieved, the revenue realization of ground water tax improved and therefore it becomes one of the locally-generated revenue of Tomohon City. Keywords : Ground-water tax, intensification, local tax, locally-generated revenue, efectiveness, efficiency.